2014
DOI: 10.1161/atvbaha.114.303922
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a-Induced Wnt1-Inducible Secreted Protein-1 Suppresses Vascular Smooth Muscle Cell Apoptosis Induced by Oxidative Stress

Abstract: Objective-Apoptosis of vascular smooth muscle cells (VSMCs) contributes to thinning and rupture of the atherosclerotic plaque fibrous cap and is thereby associated with myocardial infarction. Wnt protein activation of β-catenin regulates numerous genes that are associated with cell survival. We therefore investigated Wnt/β-catenin survival signaling in VSMCs and assessed the presence of this pathway in human atherosclerotic plaques at various stages of the disease process. Approach and Results-Wnt5a induced β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Interestingly, SMC in stable plaques in human coronary arteries showed higher staining for WISP-1 than those in unstable plaques. 79 Wnt2 also induced WISP-1 expression in SMC in β-catenin-dependent manner. 80 Levels of Wnt2 and WISP-1 were elevated in ligated carotid arteries.…”
Section: Nowak Et Al Oxidative Stress and Atherosclerosis E45mentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, SMC in stable plaques in human coronary arteries showed higher staining for WISP-1 than those in unstable plaques. 79 Wnt2 also induced WISP-1 expression in SMC in β-catenin-dependent manner. 80 Levels of Wnt2 and WISP-1 were elevated in ligated carotid arteries.…”
Section: Nowak Et Al Oxidative Stress and Atherosclerosis E45mentioning
confidence: 89%
“…78 Wnt/β-catenin/WISP-1 (WNT1-induciblesignaling pathway protein 1) represents example of the pathway that can protect SMCs from apoptosis 79 and oxidative stress but, on the other hand, enhance SMC migration and contribute to intimal thickening. 80 Mill et al 79 showed recently that macrophage-derived Wnt5a could protect SMC from H 2 O 2 -induced apoptosis. Exogenous Wnt5a increased amounts of active and nuclear β-catenin in SMC and induced TCF (transcription factor) signaling.…”
Section: Nowak Et Al Oxidative Stress and Atherosclerosis E45mentioning
confidence: 99%
“…Wnt/β-catenin responsive gene, Wnt1-inducible secreted protein-1 (WISP-1), was associated with suppression of mouse aortic SMC apoptosis induced by oxidative stress, and WISP-1 was lower in unstable, compared to stable, human atherosclerotic lesions. 90 Inhibition of Akt1 (the serine-threonine kinase) interaction with forkhead class O transcription factor 3a (FoxO3a) contributed to survival of vascular SMCs in vitro. 91 Transgenic mice with SMC-specific overexpression of Akt1 inhibited SMC apoptosis in atherosclerotic lesions without changing lesion size.…”
Section: Resident Cell Types In Atherosclerosismentioning
confidence: 99%
“…Previous studies have indicated that several miRNAs play a role in vascular physiology, including miRNA-145, miRNA-21 and miRNA-221 (15,16). However, the mechanism of regulation of SMC function by miRNAs in AAA remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study identified that Wnt5a was a direct target gene of miR-129-5p. Previous reports demonstrated that Wnt5a-induced Wnt1-inducible secreted protein-1 suppresses vascular smooth muscle cell apoptosis induced by oxidative stress (16). Wnt5a is induced by TGF-β/Smad3 in rat aortic SMC and promotes its proliferation (17).…”
Section: Discussionmentioning
confidence: 99%